Implementation of the Internal Control System in the Aviation and Space Research Organization of the National Research and Innovation Agency (BRIN) - Rita Nur Pratiwi; Afsdy Saksono; R. Luki Karunia (CV. Syntax Corporation Indonesia, 2024)
This research examines the implementation of the Internal Control System (SPI) at the Aviation and Space Research Organization (ORPA) which is under the National Research and Innovation Agency (BRIN). The aim of this research is to evaluate the effectiveness of SPI in supporting the achievement of organizational goals and identify the obstacles faced in its implementation. The research method used is descriptive qualitative with a case study approach. Data was obtained through in-depth interviews and analysis of related documents. The research results show that the implemented SPI has helped in increasing the operational accountability and transparency of ORPA BRIN. However, there are still several obstacles, such as limited human resources and policy changes that affect SPI's performance. Based on the research results, it can be concluded that the implementation of SPI in ORPA BRIN is not optimal. This is caused by deficiencies in SPI elements, such as the control environment, risk assessment, and control activities. In the control environment element, there are deficiencies in the aspects of commitment to competence, human resource development policies, the role of effective Government Internal Oversight Apparatus (APIP), and working relationships with stakeholders. This research provides recommendations for ORPA BRIN to increase human resource capacity, strengthen commitment to competence, and build close collaboration with APIP and stakeholders to support more effective implementation of SPI.